Late pregnancy ultrasound parameters identifying fetuses at risk of adverse perinatal outcomes: a protocol for a systematic review of systematic reviews. Issue 3 (23rd March 2022) - Aderoba, Adeniyi Kolade; Nasir, Naima; Quigley, Maria; Impey, Lawrence; Rivero-Arias, Oliver; Kurinczuk, Jennifer J
Abstract : Introduction: Stillbirths and neonatal deaths are leading contributors to the global burden of disease and pregnancy ultrasound has the potential to help decrease this burden. In the absence of high-Grading of Recommendations Assessment, Development and Evaluation (GRADE) evidence on universal obstetric ultrasound screening at or close to term, many different screening strategies have been proposed. Systematic reviews have rapidly increased over the past decade owing to the diverse nature of ultrasound parameters and the wide range of possible adverse perinatal outcomes. This systematic review will summarise the evidence on key ultrasound parameters in the published literature to help develop an obstetric ultrasound protocol that identifies pregnancies at risk of adverse perinatal outcomes at or close to term. Methods: This study will follow the recent Cochrane guidelines for a systematic review of systematic reviews. A comprehensive literature search will be conducted using Embase (OvidSP), Medline (OvidSP), CDSR, CINAHL (EBSCOhost) and Scopus. Systematic reviews evaluating at least one ultrasound parameter in late pregnancy to detect pregnancies at risk of adverse perinatal outcomes will be included. Two independent reviewers will screen, assess the quality including the risk of bias using the ROBIS tool, and extract data from eligible systematic reviews that meet the study inclusion criteria. Overlapping data will be assessed and managed with decision rules, and study evidence including the GRADE assessment of the certainty of results will be presented as a narrative synthesis as described in the Cochrane guidelines for an overview of reviews. Ethics and dissemination: This research uses publicly available published data; thus, an ethics committee review is not required. The findings will be published in a peer-reviewed journal. PROSPERO registration number: CRD42021266108.